2022
DOI: 10.1007/s40273-022-01132-y
|View full text |Cite
|
Sign up to set email alerts
|

The Cost Effectiveness of Levodopa-Carbidopa Intestinal Gel in the Treatment of Advanced Parkinson’s Disease in England

Abstract: Background Parkinson’s disease is a progressive neurodegenerative disease, which significantly impacts patients’ quality of life and is associated with high treatment and direct healthcare costs. In England, levodopa/carbidopa intestinal gel (LCIG) is indicated for the treatment of levodopa-responsive advanced Parkinson’s disease with troublesome motor fluctuations when available combinations of medicinal products are unsatisfactory. Objective We aimed to determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
57
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(57 citation statements)
references
References 53 publications
(101 reference statements)
0
57
0
Order By: Relevance
“…Patient data, obtained during a phase III study (NCT00335153) of CLES, was used to define the baseline distribution of patients (Supplementary Table S1). 12 The model population comprised of patients with aPD and severe motor fluctuations, defined on the Hoehn and Yahr (HY) scale as ≥3 and OFF‐time >4 hours (ie, 25% of 16‐hour waking day) 11 . The model inputs involved the subgroup of the NCT00335153 study that met these criteria and had complete follow‐up data (n = 196).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Patient data, obtained during a phase III study (NCT00335153) of CLES, was used to define the baseline distribution of patients (Supplementary Table S1). 12 The model population comprised of patients with aPD and severe motor fluctuations, defined on the Hoehn and Yahr (HY) scale as ≥3 and OFF‐time >4 hours (ie, 25% of 16‐hour waking day) 11 . The model inputs involved the subgroup of the NCT00335153 study that met these criteria and had complete follow‐up data (n = 196).…”
Section: Methodsmentioning
confidence: 99%
“…A published Markov model was adapted, 11 to determine the average costs, life years (LYs) and quality‐adjusted life years (QALYs) per patient with CLES and SoC, from the US payer perspective (using costs inputs specific for Medicare), thereby calculating the incremental cost‐effectiveness ratio (ICER). The population was redistributed into 25 disease specific health states and a death state as per the adapted model (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, a randomized, crossover design comparator study found that patients generally preferred infusion therapy with LCIG versus oral administration with levodopa ( n = 24) [ 32 ]. Indeed, meta-analyses have found significant improvements in off-time and quality of life or comparable benefits with LCIG versus deep brain stimulation, continuous subcutaneous apomorphine infusion, and best medical treatment [ 33 35 ], and similar cost between LCIG and standard of care [ 36 ].…”
Section: Introductionmentioning
confidence: 99%